Anomalous concentrations of arsenic, fluoride and radon in volcanic-sedimentary aquifers from central Italy: Quality indexes for management of the water resource. (October 2019) - Cinti, D.; Vaselli, O.; Poncia, P.P.; Brusca, L.; Grassa, F.; Procesi, M.; Tassi, F.
Abstract: 659 water samples from springs and wells in the Sabatini and Vicano-Cimino Volcanic Districts (central Italy) were analyzed for arsenic (As), fluoride (F − ) and radon ( 222 Rn) concentrations. Waters mostly sourced from a shallow and cold aquifer hosted within volcanic rocks, which represents the main public drinking water supply. Cold waters from perched aquifers within sedimentary formations and thermal waters related to a deep hydrothermal reservoir were also analyzed. The highest concentrations of As and F − were measured in the thermal waters and attributed to their enhanced mobility during water-rock interaction processes at hydrothermal temperatures. Relatively high concentrations of As and F − were also recorded in those springs and wells discharging from the volcanic aquifer, whereas waters hosted in the sedimentary units showed significantly lower contents. About 60% (As) and 25% (F − ) of cold waters from the volcanic aquifer exceeded the maximum allowable concentrations for human consumption. Such anomalously high levels of geogenic pollutants were caused by mixing with fluids upwelling through faulted zones from the hydrothermal reservoir. Chemical weathering of volcanic rocks and groundwater flow path were also considered to contribute to the observed concentrations. Cold waters from the volcanic aquifer showed the highest 222 Rn concentrations, resulting from the high contents of Rn-generating radionuclides in the volcanic units. Approximately 22% of these waters exceeded the recommended value for human consumption. A specific Quality Index (QI), comprised between 1 (very low) and 4 (very high), was computed for each water on the basis of As, F − and 222 Rn concentrations and visualized through a spatial distribution map processed by means of geostatistical techniques. This map and the specific As, F − and 222 Rn maps can be regarded as useful tools for water management by local authorities to both improve intervention plans in contaminated sectors and identify new water resources suitable for human consumption. Graphical abstract: Image 1 Highlights: Volcanic-sedimentary aquifers from Central Italy were analyzed for As, F − and 222 Rn. Water-rock interaction and input of thermal fluids are sources of geogenic pollutants. High contents of geogenic pollutants were pertaining to the volcanic aquifers. Quality Indexes (QIs) were obtained by combining the As, F − and 222 Rn concentrations. QI distribution maps can be used for water management in geogenically polluted areas. Abstract : Spatial distribution maps of geogenic pollutants (As, F − and 222 Rn) and quality indexes for water resources were determined in volcanic-sedimentary aquifers of central Italy for water management.